Introductory Statistics : student solutions manual - Ross Sheldon M.; Jaisingh Lloyd R. (San Diego Elsevier, 2005)
A work in introductory statistics, which provides an explanation of intuition and ideas behind the statistical methods. It includes a supplement which shows students how to come to the answers shown in the back of the text. It includes solutions to all of the odd numbered exercises.